DESIGNING A WAQF-BASED AGRICULTURAL FINANCING MODEL - Majid, Rifaldi; Sukmana, Raditya (Journal of Islamic Monetary Economics and Finance, 2023)
Limited access to financing, followed by the difficulty in the absorption of crop yields, is still a fundamental problem for farmers. This study proposes an integrated agricultural low-cost financing model based on cash waqf along with its parameters and risk mitigation. The proposed model is developed from a literature review underpinned by in-depth interviews with 17 experts (regulators, academia, and practitioners), followed by a Focus Group Discussion, and finally validated by the key experts. Findings reveal that cash waqf fund could be used as a low-cost financing with several risk mitigation procedures to finance farmers who have hardship accessing financing. Through institutional engineering, a nazhir (overseer) will involve a specialist vehicle in developing a value chain to facilitate off-takers ready to buy farmers’ crops at competitive prices. The proposed model employs Mudharaba-Salam and Ijara schemes. The associated risks can be mitigated by a comprehensive feasibility study, using takaful/guarantee or reserve funds and financial restructuring. This model is expected to improve farmer welfare and national food security and deepen inclusive Islamic financial products in the agricultural sector.